Factors associated with birth weight inequalities in Jordan. (1st August 2014) - Mohammad, K.; Kassab, M.; Gamble, J.; Creedy, D.K.; Foster, J.
<x xml:space="preserve">Abstract</x> Background Birth weight is a good indicator of mothers' and neonates' nutritional status, and it contributes to the newborn baby's survival, health, growth and development. Aim This study identified social factors associated with differences in the mean birth weight of newborn babies in Jordan. Methods This retrospective study analysed medical records to determine possible risk factors associated with differences in newborn BW in the Irbid governorate of Jordan. All full‐term singleton births during the year 2010 were reviewed. Abstracted data included mother's age, educational level, and monthly family income. Newborn information included birth weight, gender and birth order. Results A total of 5414 full‐term singleton births were included. Of these, 15.1% were low birth weight, 73.6% were normal birth weight, and 11.3% were high birth weight. Bivariate analysis of variance revealed that low mean birth weight was associated with female gender, first‐born babies, higher maternal age (>35 years), lower educational level and lower income (<500 JD). Multivariate analysis of variance revealed that mean birth weight was lower in female infants, first‐born infants, infants of less educated mothers, higher age and low monthly income. Limitations The findings can be generalized to full‐term singleton pregnancies in countries who share similar cultural and traditional values. Conclusion Education of mothers is a modifiable variable that can positively influence birth weight, particularly in the case of female and first‐born infants. Implication for Nursing and Health Policy The findings inform our understanding of some social factors affecting birth weights of neonates in Jordan and development of effective public health interventions that could reduce the adverse effects of such factors on newborn birth weight. Preconception and antenatal care is also important for early detection of such possible risk and targeting mothers who require early interventions and support.